David E. Mungello, Curious Land: Jesuit Accommodation and the Origins of Sinology, Studia Leibnitiana Supplementa, vol. 25, Stuttgart, 1985. Pp. 405. - Maeth Ch., Russell (Estudios de Asia y África, 1988)
-